2021
DOI: 10.1038/s41598-021-90304-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating atypical language in autism using automated language measures

Abstract: Measurement of language atypicalities in Autism Spectrum Disorder (ASD) is cumbersome and costly. Better language outcome measures are needed. Using language transcripts, we generated Automated Language Measures (ALMs) and tested their validity. 169 participants (96 ASD, 28 TD, 45 ADHD) ages 7 to 17 were evaluated with the Autism Diagnostic Observation Schedule. Transcripts of one task were analyzed to generate seven ALMs: mean length of utterance in morphemes, number of different word roots (NDWR), um proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 38 publications
2
27
1
Order By: Relevance
“…Nevertheless, several research implications of our findings and future directions are worth noting. First, using natural language processing approaches, our group has generated several automatic discourse measures that, when applied to transcripts of ADOS-2 in the same sample have shown an ability to differentiate youth with ASD from controls, both in isolation and when taken in combination ( Salem et al, 2021 ). A logical next step will be for us to compare the levels of accuracy that can be achieved, on the same subjects, by voice analysis or language analysis only, and to evaluate if combining voice and language analysis would result in gains of accuracy of predicting diagnostic status.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several research implications of our findings and future directions are worth noting. First, using natural language processing approaches, our group has generated several automatic discourse measures that, when applied to transcripts of ADOS-2 in the same sample have shown an ability to differentiate youth with ASD from controls, both in isolation and when taken in combination ( Salem et al, 2021 ). A logical next step will be for us to compare the levels of accuracy that can be achieved, on the same subjects, by voice analysis or language analysis only, and to evaluate if combining voice and language analysis would result in gains of accuracy of predicting diagnostic status.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we aimed to confirm the performance of the automated voice and language measurements as previously established by Asgari et al (2021) and Salem et al (2021), and further, to evaluate any potential gains derived from their combination. Specifically, our approach is to estimate the accuracy of a combined voice and language model in correctly classifying ASD status in a mixed sample of already-diagnosed children and a non-autistic comparison group, approaching this work with a streamlined, purposeful inclusion of established voice and language measures.…”
Section: Introductionmentioning
confidence: 88%
“…For example, Alhanai et al (2017) found that combining audio and text features increased detection of cognitive impairment in a large, longitudinal population study over both baseline demographic performance and over feature grouping. When applied to autism, NLP methods have also been used efficiently to characterize language profiles (Chojnicka & Wawer, 2020; Salem et al, 2021). Likewise, voice analyses have been performed showing discriminant prosodic patterns in autistic versus non‐autistic participant groups (Asgari et al, 2021; Kiss et al, 2012; Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a handful of studies have used computational or word frequency-based approaches to examine language produced during the ADOS-2 in autistic school-age youth (in addition to research using qualitative coding [ 81 ]). These studies focused primarily on lexico-semantic aspects of language including disfluencies [ 33 ], sentiment and linguistic abstraction [ 82 ], nouns versus cognitive process words [ 30 ], latent semantic similarity [ 83 ], number of word roots and content maze repetition [ 84 ], and acoustic-prosodic features [ 85 – 87 ]. However, children’s use of social words more broadly during the interview sections of the ADOS-2 has not been explored, and critically, only two prior studies included large enough samples of autistic girls or women to examine potential sex differences [ 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%